Collaborative management of the waqf and zakat projects syariah compliant framework for asnaf / Siti Nadiah Mohd Ali - Mohd Ali, Siti Nadiah (2022)
The State Islamic Religious Council (SIRC), the legal trustee of Malaysian waqf and zakat, is generally in charge of waqf and zakat project management. SIRC is addressing various issues, including the development of waqf land and improving the quality of life of asnaf, through high-impact and long-term projects, highlighting the shortcomings of the collaborative management platform of zakat waqf projects that are not being addressed. A syariah-compliant waqf and zakat project collaboration framework to serve as a guide for waqf and zakat management is lacking. Based on Fiqh methods, non-profit organisation collaboration theory, leadership theory, and a strategic planning framework, this thesis aims to create a syariah-compliant waqf and zakat project collaboration framework for asnaf. This collaborative framework can be used by SIRC and the Department of Waqf, Zakat, and Hajj (JAWHAR) to improve collaborative waqf and zakat projects, resulting in uniform management of waqf and zakat projects across the country. The research methodology used in this study is qualitative. The first step is to conduct a content analysis of the review of literature to determine the collaborative management strategy of waqf and zakat projects that will be used as a collaboration tool. The second method is to assess waqf-zakat collaboration projects, which employ syariah principles, non-profit collaboration, leadership, and strategic planning to produce a more comprehensive aspect of collaboration. The content analysis results reveal current and innovative strategies for collaborating on waqf and zakat projects. Meanwhile, research on waqf-zakat collaboration reveals key strategies employed by some SIRCs that others should emulate. The two findings are combined to form the basis of a collaborative waqf and zakat project. The final stage is to use the SWOT Analysis approach to evaluate the collaboration aspects of waqf and zakat projects. The assessment's findings are a valuable reflection on waqf and zakat institutions, as religious councils will gain a better understanding of their institutions' strengths and weaknesses, as well as opportunities and threats, as a result of the framework's findings. In addition, the proposed zakat waqf project collaboration framework addresses the main issues of collaboration in a syariah-compliant manner. As a result, this collaborative framework is expected to aid in the management of syariah-compliant waqf and zakat projects, improving asnaf's quality of life and making it more sustainable and targeted.